Verbotonal method in modern practice - phonetic correction of palatal lateral approximant /ʎ - Dobrić, Arnalda; Bićanić, Jordan (2014)
Despite modern ways of fast communication based mainly on written channel of communication, speech is still the most appropriate way of exchanging imformation, thoughts and emotions in humans. Pronunciation therefore holds very important place in everyday use of speech both in native and foreign languages. Still improvement of pronunciation is often neglected part in foreign language teaching and learning. In this chapter the acquisition of pronunciation and its improvement based on verbotonal method is discussed. Special attention is dedicated to the description of five basic elements of correction. The acquisition of palatal lateral approximant /ʎ/ set the example for organization of classes of phonetic correction or just parts of foreign language classes dedicated to acquisition of pronunciation. The material and procedures used from initial to final stages of correction is described and discussed. Finally, the results of acoustic analysis of the palatal lateral approximant /ʎ/ before and after lessons of phonetic correction have been discussed. The examples of the most and the least successful trainees have been given. The obtained results can be of use not only in foreign language learning but also in speech and hearing rehabilitation practice.
Projekt MZOS
ENG